Menu Costs, Posted Prices, and Multiproduct Retailers - Shantanu Dutta; Mark Bergen; Daniel Levy; Robert Venable (Journal of Money, Credit, and Banking, 1999)
We use a unique store-level data set to directly measure menu costs and to study the price change process at a large U.S. drugstore chain. We compare and contrast the magnitude of these measures with similar measures from 4 large U.S. supermarket chains. We find that (1) the actual magnitude of menu costs as a share of revenues, (2) menu costs per price change, (3) the frequent use of promotional pricing, and (4) the use of weekly pricing rules, are similar across both retail formats. Given that the main common features of these two types of retail formats are that (i) they both use posted prices, and (ii) both are multiproduct retailers selling a large number of products, our findings suggest that the magnitude of the menu cost components we measure, and the price change practices we document, may be generalizable across retail formats with these two features.
Keywords: E12; E31; 330; Menu Cost; Cost of Price Adjustment; Posted Prices; Multiproduct Retailers; Nominal Price Rigidity; Sticky Prices; Time-Dependent Pricing